Consequences of investment contract duration on the valuation of firms in maturity stage - Delgado, Madalena (2019)
Investment contract duration is a key parameter for venture capital funds operation. Variables influencing the decision around this parameter are usually treated in general principles in the classical financial literature leaving plenty of room for context sensitive research. As such, we studied variables influencing investment contract duration by investigating the performance of mature Portuguese firms that have been (partially) held by venture capital funds. Using a sample of 38 firms, sold out by venture capital funds between 1995 and 2004 we evaluated the performance of these firms using performance and sustainability indicators. We found evidence that sales growth, exports, book value, headcount and a good coverage of ISO standards implementation influenced the investment contract duration.